2013
DOI: 10.1155/2013/374342
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grazing Angle Detection in Compound-Gaussian Clutter with Hybrid MIMO Radar

Abstract: This paper focuses on the target detection in low-grazing angle using a hybrid multiple-input multiple-output (MIMO) radar systems in compound-Gaussian clutter, where the multipath effects are very abundant. The performance of detection can be improved via utilizing the multipath echoes. First, the reflection coefficient considering the curved earth effect is derived. Then, the general signal model for MIMO radar is introduced in low-grazing angle; also, the generalized likelihood test (GLRT) and generalized l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The eigenvalue decomposition (EVD) of an × Hermitian symmetric matrix requires a computation complexity of (4(1/3) 3 ) [28]. According to Section 3, the total computation complexity of an FDA MIMO radar is (5(1/3) 3 3 ), which is the same as that of a traditional MIMO radar. When the transmit and receiving arrays have the same element spacing, the computation complexity will be (5(1/3)( + ) 3 ) [29].…”
Section: Fda Mimo Radar Localization Performance and Resolution Probamentioning
confidence: 99%
See 1 more Smart Citation
“…The eigenvalue decomposition (EVD) of an × Hermitian symmetric matrix requires a computation complexity of (4(1/3) 3 ) [28]. According to Section 3, the total computation complexity of an FDA MIMO radar is (5(1/3) 3 3 ), which is the same as that of a traditional MIMO radar. When the transmit and receiving arrays have the same element spacing, the computation complexity will be (5(1/3)( + ) 3 ) [29].…”
Section: Fda Mimo Radar Localization Performance and Resolution Probamentioning
confidence: 99%
“…Multiple-input and multiple-output (MIMO) radar has received much attention in recent years. But for conventional colocated MIMO radar, the array manifold caused by time delay only depends on the angle and thus has difficulty in distinguishing the targets and interferences that have the same angle but different ranges by general beamforming techniques [1][2][3]. Moreover, the localization performance will also be significantly degraded [4,5] with the targets with the same angle but different ranges.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], the authors demonstrated that the detection performance could be significantly improved through multipath utilization with statistical MIMO radar. The detection performances of two kinds of generalized likelihood ratio test (GLRT) detectors with hybrid MIMO radar in low grazing angel were discussed in [20].…”
Section: Introductionmentioning
confidence: 99%